Environmental and biological drivers of bacterial and antimicrobial resistance carriage by house flies (Musca domestica L.) - Pickens, Victoria Lynne (My University, 2025)
House flies (Musca domestica L.) pose a significant risk to human and animal health worldwide due to their filth-associated lifecycle, mobility, and ubiquity in urban and rural environments. Frequent interactions with decaying microbe-rich organic matter used as developmental and nutritional resources for house flies results in the acquisition and movement of pathogenic and antimicrobial resistant (AMR) bacteria between environments visited for these reproductive and trophic needs. Confined cattle operations serve as an optimal environment to study fly-mediated pathogen and AMR acquisition, transmission and persistence due to the high antibiotic use, abundant bacteria sources and large house fly populations at these facilities. The first objective of this study was to assess biological and environmental drivers of bacterial abundance, as well as trends of AMR for suspected coliform (SC) bacteria carried by adult house flies in both dairy and beef cattle production facilities in Kansas. Cultured aerobic bacteria and SC were enumerated from field collected male and female flies from beef and dairy cattle operations and a subset of SC isolates were tested for susceptibility against five antibiotics to identify multi-drug resistant (MDR) bacteria. Female flies harbored more bacteria than male flies and abiotic factors such as ambient and soil temperatures correlated with both culturable bacteria and SC abundances in flies. The type of farm (beef or dairy) only correlated with SC abundance in flies. Antimicrobial resistant and MDR isolates were recovered from male and female flies from all beef and dairy operations, but SC isolates from beef flies had a notably wider range of AMR phenotypes than isolates from dairy flies. Escherichia/Shigella sp. was the most commonly identified taxa displaying AMR and MDR phenotypes. The second objective assessed biological and environmental drivers of Gram-negative bacteria abundance in house flies collected from beef cattle operations in Kansas and compared AMR Gram-negative bacteria isolated from house flies to isolates cultured from environmental substrates (manure compost, manure patties, feed, and water). Gram-negative bacteria were enumerated from cultures of male and female house fly, manure patty, feed, and water samples, followed by the selection and identification of AMR isolates after antibiotic susceptibility testing. Female flies carried greater bacterial loads than males, and bacterial abundance in flies varied between locations over time. Correlations between AMR phenotypes of Gram-negative bacteria isolated from flies and environmental samples were dependent on the location, with fly isolates typically reflecting AMR phenotypes observed in environmental isolates from the same location. Because AMR and MDR Escherichia coli were commonly observed in house flies and all environmental sample types in this study, the final objective further explored the relationship between AMR house fly and environmental isolates (manure, feed, etc.) through comparative genomics. Whole genome sequencing and predictive phylogenetic tree reconstruction of assembled isolate genomes indicated that AMR E. coli isolated from flies were closely related to isolates from manure patties, feed, and water from the same location. Furthermore, 90% of the antimicrobial resistance genes (ARGs) identified across all environmental isolates were present in the genomes of fly isolates. Additionally, observed resistance genotypes and predicted ARG mobility overlapped between AMR E. coli from flies, manure patties, feed, and water. Overall, the findings of these studies not only emphasize the environmental and biological factors influencing the role of house flies carrying and potentially disseminating microbial threats to human and animal health, but also the potential of using adult house flies for surveillance of bacteria and AMR in cattle operations.
Keywords: Musca domestica; House flies; Bacteria; Cattle; Antimicrobial resistance; Escherichia coli